Profesionalisme Guru dalam Menghadapi Transformasi Pendidikan Digital: Sebuah Studi Literatur - Irvin Rhivio; Sadrak Simanjutak; Ucok Nifandi Zakrian; Amirul Mukminin; Wijaya Putra Manalu; Fajar Sidiq (INDO PUBLISHING, 2026)
The digital transformation of education has significantly changed the educational system, particularly the roles and responsibilities of teachers as educators. The rapid development of information and communication technology requires teachers not only to master pedagogical and professional competencies but also to possess adequate digital literacy skills. This study aims to examine teacher professionalism in facing digital educational transformation through a literature review approach. The research employed a descriptive qualitative method using library research. Data were collected from various internet-based sources, including scientific journals, books, articles, and relevant documents. The data were analyzed using content analysis techniques to identify, categorize, and interpret the collected information. The findings indicate that teacher professionalism is a crucial factor in supporting the successful implementation of digital education. Digital literacy has become a fundamental competency that enables teachers to integrate technology effectively into the learning process. Furthermore, teachers face several challenges, including limited digital competencies, rapid technological advancements, digital ethics issues, and inadequate educational infrastructure. To address these challenges, various professional development strategies are needed, such as digital literacy training, participation in professional learning communities, and continuous support through school policies. Strong teacher professionalism will enhance teachers’ readiness to adapt to change and contribute to improving the quality of education in the digital era.